Outcomes of Laparoscopic Treatment Modalities for Unilateral Non-palpable Testes - Hamidi, Nurullah; Telli, Onur; Bagci, Uygar; Esen, Baris; Karagoz, Mehmet Ali; Hascicek, Ahmet Metin; Soygur, Tarkan; Burgu, Berk (Frontiers in Pediatrics, 2016)
Purpose: To date, laparoscopy has gradually become the gold standard for treatment of NPT with different success and complication rates. In this study, we aimed to evaluate outcomes of laparoscopic approaches for NPT. Materials and Methods: We reviewed data of 82 consecutive patients who underwent laparoscopic treatment for unilateral NPT at two institutions by two high volume surgeons from 2004 January to 2014 December. Laparoscopic-assisted orchidopexy(LAO) and two stage Fowler-Stephens technique(FST) was performed for 45 and 37 patients, respectively. Age(at surgery), follow-up time, laterality of testes and post-operative complications were analyzed. Modified Clavien classification system(MCCS) was used for evaluating complications. Results: The median age (at surgery) and median follow-up time were 18(range: 6-56) and 60(range: 9-130) months, respectively. Overall success rate for two laparoscopy techniques was 87.8 % during the maximal follow-up time. We observed wound infection in 2, hematoma in one, testicular atrophy in 5, testicular re-ascending in 2 patients at follow-up period. There was no statistical difference between two laparoscopic techniques for grade 1(5 vs. 2 patients, p=0.14) and grade IIIb MCCS complications(1 vs. 2 patients, p=0.44). Conclusions: Our results have shown that two laparoscopic approaches have low complication rates.